Enhancing the Storability of Coated Broccoli Heads Using Irradiated Chitosan Combined with Olive Leaves Extract (Journal of Nuclear Technology in Applied Science, 2025)
Broccoli is one of the most important nontraditional vegetable crops in Egypt. It gains its importance from its high nutritional value, but there are some obstacles facing broccoli storage such as florets yellowing, high respiration rate which lead to increase weight loss and chlorophyll degradation. thus, this experiment was carried out during the two successive seasons of 2023/2024 and 2024/2025 to evaluate the effect of both un-irradiated and irradiated chitosan (CS) with 25kGy gamma rays combined with 1 and 2% of olives leaves extract (OLE) as an edible coating to enhance the storage ability of broccoli heads under cold storage conditions (5o and 90-95% RH). Data revealed that, broccoli heads coated with irradiated chitosan with 25kGy combined with 1% followed by 2% of OLE retained the highest quality and freshness for up to 28 days, recording the the lowest weight loss percentage and decay score compared to un-coated broccoli heads. Also, it was observed that coated heads scored higher general appearance, pigment concentration (chlorophyll a, b and total chlorophyll), total soluble phenols and total free amino acids concentrations as well as total antioxidant percentage compared to uncoated broccoli heads. Thus, OLE incorporated into irradiated CS coating; relatively preserves the nutritional quality of broccoli heads during storage period.
Keywords: Broccoli; Irradiated Chitosan; Olive Leaves Extract.